2022
DOI: 10.1111/idh.12616
|View full text |Cite
|
Sign up to set email alerts
|

Influence of eight debridement techniques on three different titanium surfaces: A laboratory study

Abstract: Objectives: Debridement methods may damage implant surfaces. This in vitro study investigated eight debridement protocols across three implant surfaces to assess both biofilm removal and surface alterations. Material and Methods:One hundred sixty commercially pure titanium discs were treated to simulate commercially available titanium implant surfaces-smooth, abraded and abraded and etched. Following inoculation with whole human saliva to create a mixed species biofilm, the surfaces were treated with eight deb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Most of the studies supported the use of air polishing with glycine powder since it showed significant differences in terms of the effective removal of bacteria on implant surfaces [8,18,19,25]. One study revealed that titanium disks treated with Perioflow demonstrated less Streptococcus gordonii adhesion than the untreated surface, probably due to the difference in surface profiles observed using SEM.…”
Section: Air Polishing Device With Glycine Powdermentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the studies supported the use of air polishing with glycine powder since it showed significant differences in terms of the effective removal of bacteria on implant surfaces [8,18,19,25]. One study revealed that titanium disks treated with Perioflow demonstrated less Streptococcus gordonii adhesion than the untreated surface, probably due to the difference in surface profiles observed using SEM.…”
Section: Air Polishing Device With Glycine Powdermentioning
confidence: 99%
“…Meanwhile, another study showed varied effectiveness of sodium bicarbonate air polishing with different titanium surfaces. It was ranked as the third most effective for sandblasted, large grit, acid-etched (SLA) surfaces but was considered the least effective for both abraded and polished titanium surfaces [19].…”
Section: Air Polishing Device With Sodium Bicarbonatementioning
confidence: 99%